2016
DOI: 10.18203/2319-2003.ijbcp20162219
|View full text |Cite
|
Sign up to set email alerts
|

A drug utilization and pharmacoeconomic study of anti-diabetic drugs prescribed to type 2 diabetes mellitus patients visiting the medicine out-patient department of a tertiary care hospital of north India

Abstract: INTRODUCTIONType 2 diabetes mellitus (T2DM) is the commonest form of diabetes (responsible for >90% cases of diabetes) affecting around 422 million people in the world, and more than 80% of diabetes deaths occur in low-and middle-income countries.1 The treatment of patients with T2DM involves diet, exercise and lifestyle modifications. Those not controlled are put on oral anti-diabetic (OAD) agents, the most commonly used being sulfonylurea's and ABSTRACT Background: Type 2 diabetes mellitus (T2DM) patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…It could be due to this study being a cross sectional study captured data 2 days/ week. [12][13][14] In this study, average number of drugs was 6.6 per prescription. The WHO proposes that optimally, this should be <2.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…It could be due to this study being a cross sectional study captured data 2 days/ week. [12][13][14] In this study, average number of drugs was 6.6 per prescription. The WHO proposes that optimally, this should be <2.…”
Section: Discussionmentioning
confidence: 68%
“…Drug utilization studies conducted by Kakade A et al, and Singh A et al, showed than more than half of prescribed drugs were fixed dose combinations (60% and 71.06% respectively). 14,18 Possible reason for prescribing fixed dose combinations could be that it is convenient to take one or two pills a day rather than taking several drugs with individual formulations. But in this study it is about 50% of reported in literature, it could be due to tertiary care centre where commonly drugs available as combination have already outlived their trial.…”
Section: Discussionmentioning
confidence: 99%
“…A similar prescribing pattern of FDC was found in other studies which reported 60% and 71.06% of FDC prescription. [ 10 11 ] The reason behind the change in prescribing patterns is that pharmacotherapy for diabetes mellitus has dramatically changed in the last few years. The prescription trend is shifting toward FDCs that simplify the treatment regimen by reducing pill burden compared with the same combination delivered as separate pills.…”
Section: Discussionmentioning
confidence: 99%
“…Given the prevalence and complications of diabetes an analysis to determine the economic impact of the treatment option being prescribed in tertiary care hospital of northern India. A pharmacoeconomic study thus becomes necessary to throw light on the current approaches to the rational use of anti-diabetic drugs in type II diabetes mellitus patients visiting the medicine out-patient department, and to calculate the economic burden of different anti-diabetic therapies prescribed to patients with type II diabetes mellitus 7 . Knowledge of costs related to diabetes helps to improve understanding, addressing health care and prevention issues associated with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al7 , the cost per unit (1 mg/dl) reduction in FBG (ACER) was highest with FDC of insulin degludec and insulin aspart (INR 217.38) and lowest with FDC of glipizide and metformin (INR 10.46). Among the OADs, the ACER was highest with voglibose (INR 62.79).…”
mentioning
confidence: 99%